Correlation functions and quasi-deterministic signals - Cheremska, Nadezhda Valentinovna (Національний технічний університет "Харківський політехнічний інститут", 2023)
When processing data on random functions, they are most often limited to constructing an empirical correlation function. In this regard, the problem arises of constructing a random function (a quasi-deterministic signal) determined by a finite set of random variables and having a given correlation function. Moreover, a random function can often be considered Gaussian, since in many cases a random signal is obtained at the output of the system, which is fairly well approximated by a Gaussian. For stationary random processes and for random fields, this problem has been considered. For random sequences and discrete random fields, as well as for non-stationary random signals, the problem remained open. The article considers the problem of restoring a random sequence from known mathematical expectation and correlation function. Such a model random sequence is constructed, in which the mathematical expectation and correlation function coincide with the given ones. The mathematical expectation and the correlation function are the simplest probabilistic numerical characteristics, but they do not uniquely determine the corresponding set of probability distribution densities that satisfy the conditions of normalization and consistency, provided that for each fixed integer value of the parameter, the random sequence is a continuous random variable. The article considers the restoration of a quasi-deterministic signal in stationary and non-stationary cases. For the stationary case, three examples are given for constructing a quasi-deterministic discrete signal n , provided that the spectral density has three different forms. For the non-stationary case, the corresponding quasi-deterministic signal was obtained for various cases of the spectrum. The use of a random function model determined by a finite number of parameters makes it possible to significantly simplify the analysis of applied problems, the solution of which is associated with differential equations with random coefficients, which are such quasi-deterministic signals. In this case, there is no need to use a complex apparatus of stochastic differential equations, since the solution of such an equation simply depends on random variables as on parameters.

При обробці даних про випадкові функції найчастіше обмежуються побудовою емпіричної кореляційної функції. У зв'язку з цим виникає задача про побудову випадкової функції (квазідетермінованого сигналу), яка визначається скінченним набором випадкових величин і має задану кореляційну функцію. Причому випадкову функцію часто можна вважати гауссівською, так як у багатьох випадках на виході системи виходить випадковий сигнал, який досить добре апроксимується гауссівським. Для стаціонарних випадкових процесів та для випадкових полів це завдання було розглянуто. Для випадкових послідовностей та дискретних випадкових полів, а також для нестаціонарних випадкових сигналів проблема залишалася відкритою. У статті розглянуто завдання про відновлення випадкової послідовності за відомим математичним очікуванням та кореляційною функцією. Будується така модельна випадкова послідовність, яка має математичне очікування і кореляційна функція збігаються із заданими. Математичне очікування і кореляційна функція є найпростішими числовими ймовірнісними характеристиками, але вони не визначають однозначно відповідний набір щільностей розподілу ймовірностей, що задовольняють умовам нормування і узгодженості, за умови, що при кожному фіксованому цілому значенні параметра випадкова послідовність є неперервною випадковою величиною. У статті розглянуто відновлення квазідетермінованого сигналу у стаціонарному та нестаціонарному випадках. Для стаціонарного випадку наведено три приклади для побудови квазідетермінованого дискретного сигналу  n за умови, що спектральна щільність має три різні вигляди. Для нестаціонарного випадку отримано відповідний квазідетермінований сигнал для різних випадків спектра. Використання моделі випадкових функцій, що визначаються скінченним числом параметрів, дозволяє суттєво спростити аналіз прикладних задач, розв'язання яких пов'язане з диференціальними рівняннями з випадковими коефіцієнтами, які є такими квазідетермінованими сигналами. При цьому немає необхідності використовувати складний апарат стохастичних диференціальних рівнянь, оскільки розв’язання такого рівняння просто залежить від випадкових величин, як від параметрів.
Кореляційні функції та квазідетерміновані сигнали
Keywords: mathematical expectation; correlation function; non-stationary random function; non-stationary random sequence; quasi-deterministic signals; математичне очікування; кореляційна функція; нестаціонарна випадкова функція; нестаціонарна випадкова послідовність; квазідетерміновані сигнали